Environmental enterprises and resources development conference: Chuka University - Nderi, Alex; Ogutu, Liz; Jalango, Dorcas; Nzuki, Esther (2025)
This poster aims to share insights from the work in Kenya, where AICCRA collaborates with national and regional partners to provide tailored CIS and CSA advice, enabling farmers to manage risks and seize opportunities for more resilient agriculture. This bundled CSA and CIS practice presents an innovative decision-support tool for policy in Kenya. CSA and CIS equips AICCRA partners and the target beneficiaries - farmers with tools to build long-term resilience and manage shocks. The poster content was sourced from the AICCRA Kenya- Alliance team.